A study of peroxisome proliferator-activated receptor (PPAR) alpha in patients with ischemic heart disease and heal thy volunteers - Fong Slew, Wai (Universiti Sains Malaysia, 2008)
Ischemic heart disease (IHD) is the most common cause of cardiovascular mortality in Malaysia and around the globe. New novel biomarker, Peroxisome Proliferator-Activated Receptors-Alpha (PPAR-a) was investigated in this study to give significant contribution to early detection of IHD. In this study, we investigated the mRNA expression and protein levels of both PPAR-a and C-Reactive Protein (CRP) genes in the peripheral blood of IHD patients (n=10) and apparently healthy volunteers (n=1 0). The mRNA levels of PPAR-a (native and truncated) and CRP were determined by reverse transcription-polymerase chain reaction. The protein expression was evaluated by Western blot and measured by Enzyme linked immunosorbent assay (ELISA). The CRP mRNA expression and serum levels increased significantly (p<0.05) in IHD patients compared to normal volunteers. There was presence of both native active and truncated inhibitory PPAR-a protein in human blood leukocytes. The mRNA expressions of both native and truncated variants of PPAR-a were lower (p <0.05) in IHD patients group than those in the normal volunteers group. However, there was no significant difference (p>0.05) in PPAR-a protein level between IHD patients and normal volunteers. These findings suggest that mRNA expression level of both PPAR-a variants is decreased in IHD patients. An over-expression of the truncated inhibitory isoform of PPAR-a protein may be involved in the pathogenesis of IHD. Further study will be conducted to elucidate this matter.